Concussion knowledge, attitude and reporting intention in rugby coaches and high school rugby players. Issue 1 (February 2021) - Salmon, Danielle M; Romanchuk, Janelle; Sullivan, S John; Walters, Simon; Clacy, Amanda; Register-Mihalik, Johna K; Kerr, Zachary Y; Whatman, Chris; Keung, Sierra
The aim of this study was to evaluate New Zealand high school rugby union players' and community coaches' concussion knowledge (CK), concussion attitude (CA) and concussion reporting intentions (CRI) and to explore the impact gender, age, ethnicity, socio-economic status, experience, and concussion history had on these outcome measures. This cross-sectional study utilised the Rosenbaum Concussion Knowledge and Attitudes survey to evaluate CK, CA and CRI. The survey and demographic information were completed by 533 high school players (61.5% male, M = 16.2 yrs) and 733 community rugby coaches (93.0% male, M = 42.2 yrs). Coaches displayed greater awareness, safer attitudes, and stronger reporting intentions towards concussion than players. Among players, differences in CK, CA and CRI were observed by gender, ethnicity, and socio-economic status. Among coaches, differences in CRI were found by age and coaching experience. No differences were observed for age or concussion history in players. Gender, ethnicity, and grade coached were not significant for coaches. Players who identified as Māori or Pasifika and those from schools in low socio-economic areas displayed poorer CK and CA. Years of experience for both players and coaches played a critical role in improving CA and is a factor that should be considered when welcoming new participants to either role. Concussion non-disclosure is a systemic issue and is common across gender, ethnicity and socio-economic status and appears to worsen as the playing season progresses. More work is needed to develop educational strategies that are both culturally responsive, sustainable, and address reporting behaviours.